La place des parents et leur travail dans le parcours éducatif et thérapeutique de leur enfant en situation de handicap - Philippe Mazereau; Anne Pellissier (Anthropologie & Santé)
In France, profound changes have emerged in the approach to diseases and disabilities in a context of promoting the subjective rights of users and more broadly principles of health and social “democracy”. The place of families of children with disabilities in the development and implementation of intervention projects concerning their children has acquired an institutional legitimacy in the new legislative framework of the medico-social sector, especially through the concept of “life-project”. The traditional asymmetry between professionals and users is thus reduced. We make the hypothesis that parental activity will become more socially visible. The article draws on some of the results of a research aimed at highlighting the joint reconfigurations of the work of monitoring the pathways of young people with disabilities by families and professionals. We are interested here in the family aspect of this redefinition by restoring the place and the work of the families in the educational and therapeutic course of their child in situation of handicap.